Evoluzione dei luoghi dell’apprendimento: la residenzialità come ambito e strumento di formazione per gli studenti - Piferi, Claudio (Contesti. Città, territori, progetti, 2022)
The traditional places of learning, especially in the university and third level environment, no longer appear adequate to meet a rapidly and profoundly changing framework of demands. The recent covid-19 pandemic has in fact accentuated the necessity to rethink these places, forcing students to reinvent, adapting them, spaces designed to perform different functions: kitchens, living rooms, bedrooms, sometimes even toilets, have been transformed into classrooms, more or less virtual, with obvious deficits in the minimum requirements. The presence of smartphones, tablets or personal computers was not always enough to transform a room into a real classroom. Simultaneity of activities, no privacy, inadequate acoustics, are just some of the problems that have made learning difficult during these last two pandemic years. In addition, and not of secondary importance, ‘home learning’ has in fact made impossible that interaction, even occasional, between the students themselves and between students and teachers, which is a fundamental opportunity for the formation of a generation during an age in which sharing, meeting, and confrontation are essential tools for growth.